Cirugía maxilofacial: fractura maxilar y fístula oronasal por arma de fuego - Almansa Ruiz, José Carlos; Alvarez García, Javier; Blasco Rodríguez, Sonia (Revista Complutense de Ciencias Veterinarias, 2007)
Sin resumen